Sunset view restaurant / Saliza Sahedan... [et al.] - Sahedan, Saliza; Asmui,, Noriah; Shafii,, Rasha Azra; Syed Saffi, Syed Mohd Shaukaani; Noh, Nor Asmah (2000)
This company is formed base on partnership of 5. Sunset View Restaurant is a floating restaurant which was originally a ferry. It was converted to a floating restaurant but its original identify is still maintained. This is their effort of innovative and creativity to attract tourists from local and foreign and also surrounding populations. This restaurant is connected by a bridge to land which was built by a highest quality timber. Sunset view restaurant is located along a seaside of Batu Feringghi P.Pinang. Green surroundings and the calm sea is an important factor to bring more tourists to come to their restaurant.